INTERPRETING MOET’S 2018 GENERAL EDUCATION ENGLISH CURRICULUM - Van, Hoang Van (VNU Journal of Foreign Studies; Vol 38 No 5, 2022)
In this paper as the chief developer of the document, I will attempt to interpret and clarify some essential points of the General Education English Curriculum (GEEC) promulgated by the Vietnamese Ministry of Education and Training (MoET) on December 26, 2018. Three questions raised for exploration are: (1) “What are the backgrounds to the development and promulgation of MoET’s 2018 GEEC?”, (2) “What are the prominent characteristics of MoET’s 2018 GEEC?”, and (3) “How is MoET’s 2018 GEEC structured and why is it structured in the way it is?” These questions will be addressed in detail throughout the paper.